"Practice" as "criterion of truth" - Elza Margarida de Mendonça Peixoto (Universidade Federal de Santa Catarina, 2018)
To what, in fact, does Marx and Engel's thesis of practice as criterion of truth refer to? What is the concept of practice that effectively requires the perspective of a radical transformation of objective reality? This article considers the indications and positions of Portuguese philosopher José Adriano Barata-Moura about the movement from the idealistic dialectic to Marx's materialist dialectic, in which the perspective of practice as material transformation is understood to be central. The article then conducts a direct reading of works by Marx, in some cases those written in conjunction with Engels, between 1843 and 1846 (the period close to the writing of the Theses on Feuerbach) which reveal the movement of criticism of idealistic understandings of the dialectic and of positivist materialism.